Proceedings of the 45th International Symposium on Symbolic and Algebraic Computation 2020
DOI: 10.1145/3373207.3404035
|View full text |Cite
|
Sign up to set email alerts
|

Signature-based algorithms for Gröbner bases over tate algebras

Abstract: Introduced by Tate in [Ta71], Tate algebras play a major role in the context of analytic geometry over the p-adics, where they act as a counterpart to the use of polynomial algebras in classical algebraic geometry. In [CVV19] the formalism of Gröbner bases over Tate algebras has been introduced and e ectively implemented. One of the bottleneck in the algorithms was the time spent on reduction, which are signi cantly costlier than over polynomials. In the present article, we introduce two signature-based Gröbne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In earlier papers [6,7], the authors showed that it is possible to define and compute Gröbner bases of Tate ideals with coefficients in Z or Q , and that the definitions are compatible with the usual theory on polynomials over the residue field F or over the coefficient ring. A major limitation of the algorithms designed in loc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In earlier papers [6,7], the authors showed that it is possible to define and compute Gröbner bases of Tate ideals with coefficients in Z or Q , and that the definitions are compatible with the usual theory on polynomials over the residue field F or over the coefficient ring. A major limitation of the algorithms designed in loc.…”
Section: Introductionmentioning
confidence: 99%
“…is the increasing cost of reductions as the precision grows. Our previous paper [7] addresses the case of expensive reductions to zero, through the use of signature algorithms, but computing the result of nontrivial reductions remains expensive. Another question left open was whether it is possible to exploit overconvergence properties, namely the knowledge that the series we are working with satisfy a stronger convergence condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier papers [CVV19,CVV20], the authors showed that it is possible to define and compute Gröbner bases of Tate ideals with coefficients in Z or Q , and that the definitions are compatible with the usual theory on polynomials over the residue field F or over the coefficient ring. A major limitation of the algorithms is the increasing cost of reductions as the precision grows.…”
Section: Introductionmentioning
confidence: 99%
“…A major limitation of the algorithms is the increasing cost of reductions as the precision grows. Our previous paper [CVV20] addresses the case of expensive reductions to zero, through the use of signature algorithms, but computing the result of non-trivial reductions remains expensive. Another question left open was whether it is possible to exploit overconvergence properties, namely the knowledge that the series we are working with satisfy a stronger convergence condition.…”
Section: Introductionmentioning
confidence: 99%